Let’s end taxonomic blank slates with molecular morphology - Tessler, Michael; Galen, Spencer C.; DeSalle, Rob; Schierwater, Bernd (Frontiers in Ecology and Evolution, 2022)
Many known evolutionary lineages have yet to be described formally due to a lack of traditional morphological characters. This is true for genetically distinctive groups within the amoeboid Placozoa animals, the protists in ponds, and the bacteria that cover nearly everything. These taxonomic tabula rasae, or blank slates, are problematic; without names, communication is hampered and other scientific progress is slowed. We suggest that the morphology of molecules be used to help alleviate this issue. Molecules, such as proteins, have structure — they are even visualizable with X-ray crystallography — albeit more easily detected by and easier to work with using genomic sequencing. Given their structured nature, we believe they should not be considered as anything less than traditional morphology. Protein-coding gene content (presence/absence) can also be used easily with genomic sequences, and is a convenient binary character set. With molecular morphology, we believe that each taxonomic tabula rasa can now be solved.